INVESTIGATING THE THERMAL REGIME OF THE BIOGAS-HEAT PIPE REACTOR - Khusenov , A.A.; Ergashev , Sh.H.; Norboev, Z.Kh.; Boynazarov , R. (Muqobil energetika, 2023)
the heat balance of the reactor of the biogas-heat pipe device is compiled in the article. Based on this balance equation, a mathematical model of air and biomass temperature change is presented. It has been determined that the temperature of the heated air due to solar energy passing through the clear surface of the biogas-heat pipe device is heated up to 85-95℃, and as a result of the heating of the biomass inside the device, the process of anaerobic fermentation continues. It has been proven on the basis of experimental results that this heat can be transferred to the greenhouse through the heat carrier inside the heat pipe and provide the temperature regime of the greenhouse. As a result, it is based on the fact that the biogas-heat pipe device can fully cover the heat load during the heating season of the greenhouse. It is shown in the graphs that the results of the experimental study differ by 4-6% from the results of modeling.